Retrofits for Energy Efficient Office Buildings: Integration of Optimized Photovoltaics in the Form of Responsive Shading Devices - Abdullah, Hardi K.; Alibaba, Halil Z. (Mdpi, 2017)
This study presents a retrofit strategy: integrating optimized photovoltaics (PV) in the form of responsive shading devices using a dual-axis solar tracking system. A prototype-based model was fabricated to compare the efficiency of PV in this implementation with the conventional fixed installation. The office building, T1 Empire World in Erbil, was selected as a retrofit case study and for the application of the proposed integration system. In order to assess the effectiveness of the proposed retrofit method, the energy performance of the base case is simulated to be compared later with the energy performance simulations after the integration technique. The amount of generated electricity from the PV surfaces of the integrated shading elements is calculated. The energy simulations were performed using OpenStudio((R)) (NREL, Washington, DC, USA), EnergyPlus(TM) (NREL, Washington, DC, USA), and Grasshopper/ Ladybug tools in which the essential results were recorded for the baseline reference, as well as the energy performance of the retrofitted building. The results emphasize that the PV-integrated responsive shading devices can maximize the efficiency of PV cells by 36.8% in comparison to the fixed installation. The integrated system can provide approximately 15.39% of the electricity demand for operating the building. This retrofit method has reduced the total site energy consumption by 33.2% compared to the existing building performance. Total electricity end-use of the various utilities was lowered by 33.5%, and the total natural gas end-use of heating demand was reduced by 30.9%. Therefore, the percentage reduction in electricity cooling demand in July and August is 42.7% due to minimizing the heat gain in summer through blocking the sun's harsh rays from penetrating into interior spaces of the building. In general, this system has multiple benefits, starting with being extremely efficient and viable in generating sustainable alternative energywhich is the global growing concern of today's sustainable developmentproviding thermal comfort for occupants, and granting a dynamic appearance to the building when the PV-integrated elements rotate according to the sun's position in the sky.
Keywords: building retrofit; photovoltaic optimization; responsive shading devices; energy efficiency; office building